Implications of early diagnosis of autosomal dominant polycystic kidney disease: a post hoc analysis of the TEMPO 3:4 trial - Janssens, Peter; Jouret, François; Bammens, Bert; Liebau, Max C.; Schaefer, Franz; Dandurand, Ann; Perrone, Ronald D.; Müller, Roman-Ulrich; Pao, Christina S.; Mekahli, Djalila (Scientific reports, 2020)
It is unknown whether early diagnosis of autosomal dominant polycystic kidney disease (ADPKD) can enable earlier management and improve outcomes. We conducted a post hoc analysis of data from the TEMPO 3:4 trial. Subjects were stratified by ADPKD diagnosis at age ≤18 (childhood diagnosis [CD]) or>18 (adulthood diagnosis [AD]). Groups were compared for baseline characteristics and total kidney volume (TKV) growth and estimated glomerular filtration rate (eGFR) decline over 3 years. 294 CD and 1148 AD subjects were analyzed. At inclusion, CD subjects were younger (mean age 34.2 versus 39.8 years; p < 0.0001) and had better eGFR (mean ± SD 87.4 ± 23.9 versus 80.1 ± 20.7 mL/min/1.73 m2; p < 0.0001), while CD had more severe Mayo risk classification (p < 0.0001) and more PKD1 mutations (p = 0.003). No statistical differences were found in TKV or eGFR change. At study end, placebo-treated CD subjects had better eGFR than projected by a prediction equation (mean difference ±SD for observed versus predicted eGFR: 2.18 ± 10.7 mL/min/1.73 m2; p = 0.0475). However, these results are not confirmed when excluding stage 1 CKD. Whether CD subjects, despite their risk profile, have a slower disease course than predicted remains inconclusive. Future studies are needed to confirm that early diagnosis and management can alter the disease course of ADPKD.
Gesehen am 29.10.2020